Phylogenetic study of Geitlerinema and Microcystis (Cyanobacteria) using PC-IGS and 16S-23S ITS as markers: Investigation of horizontal gene transfer - Piccin-Santos, Viviane [UNESP]; Brandão, Marcelo Mendes; Bittencourt-Oliveira, Maria Do Carmo (Wiley, 2014)
Selection of genes that have not been horizontally transferred for prokaryote phylogenetic inferences is regarded as a challenging task. The markers internal transcribed spacer of ribosomal genes (16S-23S ITS) and phycocyanin intergenic spacer (PC-IGS), based on the operons of ribosomal and phycocyanin genes respectively, are among the most used markers in cyanobacteria. The region of the ribosomal genes has been considered stable, whereas the phycocyanin operon may have undergone horizontal transfer. To investigate the occurrence of horizontal transfer of PC-IGS, phylogenetic trees of Geitlerinema and Microcystis strains were generated using PC-IGS and 16S-23S ITS and compared. Phylogenetic trees based on the two markers were mostly congruent for Geitlerinema and Microcystis, indicating a common evolutionary history among ribosomal and phycocyanin genes with no evidence for horizontal transfer of PC-IGS. Thus, PC-IGS is a suitable marker, along with 16S-23S ITS for phylogenetic studies of cyanobacteria. © 2014 Phycological Society of America.
Keywords: 16S-23S ITS; Cyanobacteria; Lateral gene transfer; Molecular phylogeny; Phycocyanin; Ribosomal genes